EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS XI - izzah, siti laylatul (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2020)
The Effectiveness of Group Investigation Learning Models on Student Learning Outcomes in Subjects of Fiqh. The purpose of this research is to find out whether the group investigation learning model class XI MIPA is more effective than the conventional learning model class XI IIS 1 on the learning outcomes of students of class XI Aliah Al-Ihsan Kalikejambon on Fiqh subjects. The research is in the form of experiments with the type of experiment conducted is quasi-experimental research (Quasy Experiment Research). Based on the results of statistical calculations from the average post-test results of the control class 68.35 and the average post-test results of the experimental class 72.75 obtained calculations using the SPSS program with a significance of significance (Sig 2-tailed) is 0.034, a significance value of 0.034 <0.05. Then Ho is rejected and Ha is accepted. Thus it can be concluded that there is a significant difference between the results of the post-test of the control class and the experimental class. Thus, it can be said that the teaching and learning process carried out with the group investigation learning model in class XI MIPA is more effective than conventional learning models in class XI IIS 1 on student learning outcomes in the subject of Fiqh. Keywords: Fiqh lessons, Group Investigation, Learning Outcomes Abstrak Efektivitas Model Pembelajaran Group Investigation Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqih. Tujuan dilakukannya penelitian ini adalah untuk mengetahui apakah model pembelajaran group investigation kelas XI MIPA lebih efektif dibandingkan dengan model pembelajaran konvensional kelas XI IIS 1 terhadap hasil belajar siswa kelas XI Madrasah Aliah Al – Ihsan Kalikejambon pada mata pelajaran Fiqih. Adapun penelitian ini berbentuk eksperimen dengan jenis eksperimen yang dilakukan adalah penelitian eksperimen semu (Quasy Experiment Reasearch). Berdasarkan hasil perhitungan statistik dari rata-rata hasil post-test kelas kontrol 68,35 dan rata-rata hasil post-test kelas eksperimen 72,75 diperoleh perhitungan menggunakan program SPSS dengan signifikansi signifikansi (Sig 2-tailed) adalah 0,034, nilai signifikansi 0,034 < 0,05. Maka Ho ditolak dan Ha diterima. Dengan demikian dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara hasil post-test kelas kontrol dan kelas eksperimen. Dengan demikian, dapat dikatakan bahwa proses belajar mengajar yang dilakukan dengan model pembelajaran group investigation di kelas XI MIPA lebih efektif daripada model pembelajaran konvensional di kelas XI IIS 1 terhadap hasil belajar siswa pada mata pelajaran Fiqih. Kata kunci: Pelajaran Fiqih, Group Investigation, Hasil Belajar